Relation of adaptive and maladaptive perfectionism to behavioral activation, behavioral inhibition, and heart rate variability - Corson, Ansley T. (East Carolina University, 2016)
Background: Recent research has indicated that different subtypes of perfectionism are differentially related to stress, coping, and psychophysiology, with individuals who exhibit higher levels of maladaptive perfectionism having increased levels of stress, maladaptive coping, and fatigue, as well as elevated blood pressure and cortisol levels in response to stressful tasks. The opposite pattern has been found to hold true for individuals displaying greater levels of adaptive perfectionism. An additional set of multidimensional personality traits that have been associated with differential psychophysiological outcomes and perfectionism are the behavioral inhibition system and behavioral activation system (BIS/BAS). Purpose: The current research seeks to understand the possible relations between adaptive and maladaptive perfectionism, BIS/BAS, and cardiac autonomic activity, particularly heart rate variability (HRV). Methods: 1,214 healthy undergraduate students were asked to complete a series of online self-report inventories related to perfectionism and behavioral approach and avoidance. One hundred and twenty-two eligible students were then asked to complete an initial 10-minute baseline recording of heart rate and blood pressure, followed by a 15-minute anagram stressor task, and then a 10-minute recovery-period recording. Additionally, they were asked to complete a measure of state affect both before and after the electrophysiological recordings. Results: Results indicated that there was no statistically significant association between perfectionism classification and baseline HRV, nor between perfectionism classification and changes in HRV from baseline, either during the stressor task or during the recovery period. Additional results indicated that male adaptive perfectionists had significantly higher BIS-Total scores than nonperfectionists and maladaptive perfectionists, that female nonperfectionists and adaptive perfectionists had significantly higher BIS-Total scores than maladaptive perfectionists, that both male and female nonperfectionists had significantly higher BAS-Total, BAS-Drive, and BAS-Reward-Responsiveness scores than adaptive and maladaptive perfectionists, and that male nonperfectionists and adaptive perfectionists had significantly higher BAS-Fun-Seeking scores than maladaptive perfectionists. Finally, results indicated that baseline HRV scores could not be significantly predicted by BIS-Total, BAS-Reward-Responsiveness, and BAS-Drive scores. Discussion: The current research found that there were no significant relations between either perfectionism and HRV, or BIS/BAS and HRV. However, significant relations were found between adaptive and maladaptive perfectionism and BIS/BAS, though not in the hypothesized direction. Instead, it was found that BAS was more related to nonperfectionism and BIS to adaptive perfectionism. As these results appear consistent in light of revised RST, future research on the relations between perfectionism and BIS/BAS should utilize revised RST in theory formulation and measurement.
Keywords: heart rate variability; behavioral inhibition/behavioral activation; Perfectionism (Personality trait); Stress (Psychology)--Testing; Heart beat; Behavioral assessment